The Role of Unboxing Content on TikTok in Shaping Purchase Intention Toward Blind Box Products - Karen Talenta Gracia Perangin-angin; Sumardjijati Sumardjijati; Ratih Pandu Mustikasari (Indonesian Journal Publisher, 2026)
Unboxing content on TikTok has evolved into one of the persuasive communication strategies associated with consumer purchase intention toward blind box products, in line with the growing popularity of surprise-based collectible products among social media users. This study aims to examine the relationship between unboxing content on the TikTok account @asakecil and purchase intention toward blind box products among its followers, drawing on the Elaboration Likelihood Model (ELM) proposed by Petty and Cacioppo (1986) as the theoretical framework for understanding how persuasive messages are processed through both the central and peripheral routes. Data were collected through an online questionnaire distributed to 100 active followers of the TikTok account @asakecil, selected using simple random sampling, and were analyzed using Spearman's Rank correlation test through the SPSS program. The results reveal a positive and significant relationship, at a moderate level of correlation, between unboxing content on TikTok @asakecil and purchase intention toward blind box products among its followers, as indicated by a Spearman correlation coefficient of 0.400 with a significance value of 0.000 (p < 0.05). This study affirms that unboxing content functions not merely as entertainment but also as a persuasive communication medium that plays a role in shaping consumer purchase intention in the digital era.